Karakteristik dan Periode Kekambuhan Stroke pada Pasien dengan Stroke Berulang di Rumah Sakit Margono Soekardjo Purwokerto Kabupaten Banyumas - Meida Laely Ramdani (Jurnal Keperawatan Muhammadiyah, 2018)
Background: Patients who had stroke recurrence after the first stroke have a high risk of disability as well as high rates of morbidity and mortality. Incidence of stroke recurrence can be prevented by controlling risk factors and secondary prevention among post stroke patient, and also tent of the duration of the occurrence of recurrent stroke after the first attack. Objective: The purpose of this study was to determine the characteristics and stroke recurrence periods of post stroke patients.Methods: Cross sectional study design was used in this study. Total 73 recurrent stroke patients age 18-60 years old were selected using consecutive sampling technique. This study was conducted on patients during their follow up in the outpatient department of unit neurology, Margono Soekardjo Purwokerto Hospital during November-December 2015. The characteristics of the recurrent stroke patients include sex, age, education, occupation, and income. This study also describes type of stroke and duration of illness. The periods of recurrent stroke patients divided in to three time periods (≤ 6-month, 7-12 month, >12 month). Results: 73 recurrent stroke patients showed 56% were female, age group 39-60 years old was 97,5%, 60,3% have low education (below senior high school), 64,7% work as public and private employees. Income of respondents were low income 53,4%. Ischemic stroke was the majority (87,7%), no history family of stroke 64,4%, 1-5 years duration of illness and periods of stroke recurrence >12 month was 45,20%.Conclusion:  Ischemic stroke is the biggest case of recurrent stroke, so that we need to emphasize the importance of secondary prevention including medication and treatment. Background: Patients who had stroke recurrence after the first stroke have a high risk of disability as well as high rates of morbidity and mortality. Incidence of stroke recurrence can be prevented by controlling risk factors and secondary prevention among post stroke patient, and also tent of the duration of the occurrence of recurrent stroke after the first attack. Objective: The purpose of this study was to determine the characteristics and stroke recurrence periods of post stroke patients.Methods: Cross sectional study design was used in this study. Total 73 recurrent stroke patients age 18-60 years old were selected using consecutive sampling technique. This study was conducted on patients during their follow up in the outpatient department of unit neurology, Margono Soekardjo Purwokerto Hospital during November-December 2015. The characteristics of the recurrent stroke patients include sex, age, education, occupation, and income. This study also describes type of stroke and duration of illness. The periods of recurrent stroke patients divided in to three time periods (≤ 6-month, 7-12 month, >12 month). Results: 73 recurrent stroke patients showed 56% were female, age group 39-60 years old was 97,5%, 60,3% have low education (below senior high school), 64,7% work as public and private employees. Income of respondents were low income 53,4%. Ischemic stroke was the majority (87,7%), no history family of stroke 64,4%, 1-5 years duration of illness and periods of stroke recurrence >12 month was 45,20%.Conclusion:  Ischemic stroke is the biggest case of recurrent stroke, so that we need to emphasize the importance of secondary prevention including medication and treatment.